Parents' Hesitancy to Vaccinate Their 5–11-Year-Old Children Against COVID-19 in Saudi Arabia: Predictors From the Health Belief Model - Almalki, Ohoud S.; Alfayez, Osamah M.; Al Yami, Majed S.; Asiri, Yousif A.; Almohammed, Omar A. (Frontiers in Public Health, 2022)
Data exploring parents' hesitancy to vaccinate their 5–11-year-old children against COVID-19, and associated factors, is limited. This study aims to investigate parents' beliefs and intentions to vaccinate their 5–11-year-old children using the Health Belief Model in Saudi Arabia. A national, cross-sectional, questionnaire-based study was conducted in November, 2021. The self-administered online questionnaire was distributed to a random sample of parents. Adult parents with at least one 5–11-year-old child were included. The main outcome was parents' intention to vaccinate their 5–11-year-old children. Variability in parents' intention was assessed by demographics, COVID-19-related factors, children's health status, and constructs from the Health Belief Model. Univariate and multivariable logistic regression were used to investigate each factor and adjust for the intervariable effect on parental intention to vaccinate their children. Of the 4,135 participants, 61.9% were hesitant to vaccinate their 5–11-year-old children. Parents aged 31 to 40 years (OR = 1.23; 95% CI, 1.02–1.49) and females (OR = 1.52; 95% CI, 1.25–1.84) had higher odds of being hesitant to vaccinate their children than parents from other groups. Parents who perceived low benefit from the vaccine (OR = 16.3; 95% CI, 12.1–21.9) or who had safety or efficacy concerns (OR = 3.76; 95% CI, 3.10–4.58) were among the most hesitant to vaccinate their children. In conclusion, vaccine hesitancy is prevalent among parents of 5–11-year-old children in Saudi Arabia and those who had beliefs of minimal benefits or lack of safety from the COVID-19 vaccine were more hesitant. Government efforts must be directed toward increasing parents' vaccine awareness and tackling the constructs of the Health Belief Model through a well-designed vaccination campaign.